Nematology Lab - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Adewuyi, a nematologist, takes students on a tour around the nematology laboratory where the effects of nematodes on plants and soil are determined to provide necessary information for breeders to produce disease(nematodes)resistant plants. Some equipment found in the laboratory are: 1. Incubator for incubating nematodes 2. Compound Microscope for view nematodes 3.Laminar flow for culturing 4. Steam sterilizer machine to sterilized soil.